The Sagebrush State, 4th Ed : Nevada's History, Government, and Politics - Bowers, Michael Wayne (Book collections on Project MUSE., 2013)
Nevada's politics have been formed in large measure by its turbulent history and harsh environment. This volume explains the dynamics of this process, which is strikingly unique among the fifty states. This is an explanation of how Nevada's history has formed its political culture, and how its government works. The book includes the full text of the state constitution, with extensive annotations of all amendments to the original 1864 document. This book serves as a text for the study of Nevada's history and constitution, which is a graduation requirement at the state's colleges and universities. The fourth edition of this work has been updated through 2012 to include information on the elections of 2010 and 2012, and on controversial sessions of the Legislature. --